2021
DOI: 10.1128/mbio.03679-20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immunoglobulin Isotype and Epitope on the Functional Properties ofVibrio choleraeO-Specific Polysaccharide-Specific Monoclonal Antibodies

Abstract: Vibrio cholerae causes the severe diarrheal disease cholera. Clinical disease and current oral cholera vaccines generate antibody responses associated with protection. Immunity is thought to be largely mediated by lipopolysaccharide (LPS)-specific antibodies, primarily targeting the O-antigen. However, the properties and protective mechanism of functionally relevant antibodies have not been well defined. We previously reported on the early B cell response to cholera in a cohort of Bangladeshi patients, from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
(79 reference statements)
2
10
0
Order By: Relevance
“…This is in agreement with a previous finding, in which a waaL mutant that lacks O-antigen also had impaired motility, affecting the ability of V. fischeri to spread in soft agar [35]. In addition, LPS-specific, antibody-mediated motility arrest, at the level of the individual V. cholerae bacterium, has been demonstrated to effectively inhibit cholera dispersal or provide protection in vivo [36]. O-antigen is considered a major virulence factor that is required, for instance, in vertical localization, small intestine colonization, and resistance to the immune response and antibiotics [32].…”
Section: Implications Of Phage Resistance For Bacterial Physiological...supporting
confidence: 93%
“…This is in agreement with a previous finding, in which a waaL mutant that lacks O-antigen also had impaired motility, affecting the ability of V. fischeri to spread in soft agar [35]. In addition, LPS-specific, antibody-mediated motility arrest, at the level of the individual V. cholerae bacterium, has been demonstrated to effectively inhibit cholera dispersal or provide protection in vivo [36]. O-antigen is considered a major virulence factor that is required, for instance, in vertical localization, small intestine colonization, and resistance to the immune response and antibiotics [32].…”
Section: Implications Of Phage Resistance For Bacterial Physiological...supporting
confidence: 93%
“…OSP-specific antibody responses inhibit V. cholerae motility, and this effect may be mechanistically involved in protection against cholera within the intestinal lumen of infected humans [41] . Blocking the ability of the highly mobile and freely-swimming V. cholerae pathogens from reaching their target ecological niche within the intestinal lumen of infected humans and delivering cholera toxin to intestinal epithelial cells may be protective [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Much effort is now being made to assess how OSP-specific antibodies might protect against cholera, with a growing body of evidence suggesting that protection against infection may involve the ability of OSP-specific antibodies to impede the motility of V. cholerae organisms in the human intestine. This effect requires at least two-point binding of OSP-specific antibodies [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: V Cholerae -Antigen Repertoirementioning
confidence: 99%
“…There is no evidence that enhanced opsonophagocytosis or antibody-dependent cytotoxic activity in the intestinal lumen plays a role in mediating protection against cholera. Although cell-free antibody-based killing via complement lysis might be considered possible in the intestinal lumen, viability studies in animals have shown that bactericidal activity is not required for protection from disease [ 22 , 25 , 26 ]. In addition, although C3 and earlier components of the complement cascade have been detected in the intestinal lumen/epithelium, the terminal components of the complement cascade have not been detected in the lumen in the absence of epithelial breakdown and intestinal inflammation [ 38 , 39 , 40 ].…”
Section: Correlates Of Protectionmentioning
confidence: 99%
See 1 more Smart Citation